Analisis Pengembangan Model Bisnis Kanvas CV Kandura Keramik Bandung - Permadi, Benedictus; Nurmalina, Rita; Kirbrandoko, Kirbrandoko (Universitas Brawijaya, Indonesia, 2016)
CV Kandura Keramik is one of companies which runs its business in ceramicÂ production. As a company which is producing ceramics with high market potential, theÂ company needs capacity building by identifying internal and external factors in order toÂ facilitate in improving the company's internal management and to develop strategies thatÂ can be used optimally to improve the company's revenue. This research is aiming to give anÂ overview of the business model performed by CV Kandura Ceramic along with the overviewÂ of Strengths, Weaknesses, Opportunities and Threats based on Business Model Canvas andÂ provide input regarding corrective measures for the company. Research method conductedÂ with Business Model Canvas approach and SWOT analysis to allow the formation of alternativeÂ strategy. The improvement of business model performed on seven of nine elements of BMCÂ and there are seven major improvement programs for the company as follows: Establish aÂ new segmentation, cooperation with art students, business partners, suppliers and partners,Â registering products to Standardization Agency, form R&D subdivision andÂ human resources.